Physical characteristics test (water content and viscosity) of extraction sodium alginate brown algae (phaeophyta) species padina sp. as basic material for production dental impression material - Nurlindah Hamrun; Bahruddin Thalib; Dahlang Tahir; Syaharuddin Kasim; Ahmad F. Nugraha (DiscoverSys Inc., 2018)
Objective: This research aims to explore the potential of brown algae species padina sp. as a dental impression material by examining the physical characteristics of the sodium alginate extraction of brown algae species padina sp.Material and Methods: This research is a quasi-experimental with one-shot case study design. Samples are brown algae species padina sp. from Punaga and Puntondo beach in South Sulawesi. Brown algae species padina sp. is extracted to obtain sodium alginate and further tested for physical characteristics including viscosity test and water content.Results: The extraction of brown algae species padina sp. resulted in 250 grams (25%) of brown powdered sodium alginate that smelled fishy. Physical characteristic tests revealed the water content of sodium alginate species from brown algae padina sp. was 8%. This result is acceptable for sodium alginate water content as set by the Food Chemical Codex that requires less than 15% water content. The measurement of the viscosity obtained is 13.33 cps.Conclusion: These results indicate that the species of brown algae padina sp. has the potential to be one of the basic materials of dental impression material.